Exoskeleton therapy in cerebral palsy: improved gait endurance without kinematic change - Chmara, Paweł; Brazevic, Sabina; Jóźwiak, Marek; Chen, Brian Po-Jung; Manikowska, Faustyna (Frontiers in Human Neuroscience, 2025)
IntroductionCerebral palsy (CP) often leads to impairments in movement and posture, limiting functional mobility. Robotic-assisted gait training (RAGT) using powered exoskeletons has emerged as a novel approach to enhance gait in individuals with CP. However, evidence regarding its effectiveness, particularly in unassisted gait performance, remains limited and inconclusive.MethodsThis study involved 44 ambulatory youth with bilateral hypertonic CP (GMFCS levels I–III), who underwent an intensive RAGT program using the EksoGT exoskeleton. The intervention consisted of 28 sessions (90 min each) over 8 weeks, with a 2 weeks mid-point break. Gait assessments were conducted before (T1) and after (T2) therapy using 3D motion analysis and the 6-minute walk test (6MWT). Primary outcomes included spatiotemporal parameters, gait symmetry, gait deviation index (GDI), and walking endurance.ResultsFollowing the exoskeleton training, participants demonstrated a statistically significant improvement in gait efficiency, with 6MWT distances increasing from 375 to 418 m (p < 0.01). However, no significant changes were observed in gait symmetry, spatiotemporal parameters, or GDI scores, indicating no measurable effect on unassisted gait mechanics.ConclusionIntensive exoskeleton therapy significantly improved walking endurance but did not alter gait symmetry or kinematics in independently ambulatory youth with hypertonic CP. These - findings suggest that while exoskeleton assisted training enhances functional endurance, its impact on gait pattern may be limited. Further research should explore its broader benefits on quality of life, participation, and psychosocial outcomes.